2013
DOI: 10.1097/mop.0b013e32835c2b42
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis and septic arthritis in children

Abstract: Up to date knowledge of emerging pathogens, utilization of modern diagnostic techniques and implementation of new shorter treatment regimens can optimize the treatment of pediatric septic arthritis and osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(183 citation statements)
references
References 38 publications
3
143
0
9
Order By: Relevance
“…MRI is an important early tool to determine location and extent of infection as well as assist with preoperative planning when surgically significant complications of osteomyelitis are identified [1][2][3]. One quandary regarding MRI is whether the presence of joint effusion, in the setting of nearby metaphyseal osteomyelitis, represents an innocuous, non-pyogenic reactive effusion or concurrent septic arthritis.…”
Section: Introductionmentioning
confidence: 98%
“…MRI is an important early tool to determine location and extent of infection as well as assist with preoperative planning when surgically significant complications of osteomyelitis are identified [1][2][3]. One quandary regarding MRI is whether the presence of joint effusion, in the setting of nearby metaphyseal osteomyelitis, represents an innocuous, non-pyogenic reactive effusion or concurrent septic arthritis.…”
Section: Introductionmentioning
confidence: 98%
“…[10][11][12] The results showed that a 4-day course of adjuvant dexamethasone shortened the duration of symptoms and hospital stay and reduced residual dysfunction at the end of therapy. The rationale for the dosing schedule was derived from the Haemophilus influenzae B meningitis protocol 13 ; the use of corticosteroids was prompted by findings of a decrease in synovial T-cell and macrophage levels in animals with septic arthritis treated with dexamethasone and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…12,20 Neonatal age, immunosuppressive diseases, hip joint involvement, delay in antibiotic treatment, and MRSA infection are known predictors of complications. 20 In the current study, no complications of septic arthritis other than osteomyelitis were documented from discharge to the last clinic visit (minimum 6 months) in the patients selected for the study.…”
Section: Discussionmentioning
confidence: 99%
“…1,24 Studies conducted in California, 21 Tennessee 22 and Texas 23 have reported S. aureus as the most common pathogen of osteoarticular infection in children, with proportions ranging from 40% to 85%. However, in contrast to those earlier studies, we used a highly sensitive technique to identify K. kingae in the joint aspirate samples.…”
Section: Discussionmentioning
confidence: 99%